1998
DOI: 10.3758/bf03208004
|View full text |Cite
|
Sign up to set email alerts
|

The effect of timing and spatial separation on the velocity of auditory apparent motion

Abstract: Previously, it was shown that the minimum conditions for the illusion of auditory apparent motion (AAM) depend on stimulus timing hut not spatial separation. In the present experiment, the effects of stimulus timing and source separation on the perceived velocity of AAM were examined. Eight listeners estimated the velocity, duration, and distance traveled of AAM, using a no-modulus, magnitude estimation procedure. Four burst durations (25, 50,100, and 300 msec), 10stimulus onset asynchronies (SOAs; 30, 40, 50,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 24 publications
2
7
0
Order By: Relevance
“…This result agrees with the data reported by Strybel et al (1998), where authors estimated the duration and separation between the sources to determine whether the velocity of AAM could be predicted from these estimates. It was found that the perception of velocity of apparent motion was mainly affected by stimulus timing.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This result agrees with the data reported by Strybel et al (1998), where authors estimated the duration and separation between the sources to determine whether the velocity of AAM could be predicted from these estimates. It was found that the perception of velocity of apparent motion was mainly affected by stimulus timing.…”
Section: Discussionsupporting
confidence: 93%
“…It was found that the perception of velocity of apparent motion was mainly affected by stimulus timing. Physical separation also affected perceived velocity, but the effect was small (Strybel et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…An argument for the snapshot theory is that a sound source does not need to actually move to create the sensation of movement. The proper timing of two acoustic stimuli produced from two separate sound sources can produce the sensation of sound source motion called auditory apparent motion (AAM) (Strybel et al, 1998). Stimulus timing is determined from the durations of both stimuli and the difference in their onset times, called stimulus onset asynchrony (SOA).…”
Section: Perception Of Moving Sound Sourcesmentioning
confidence: 99%
“…Stimulus timing is determined from the durations of both stimuli and the difference in their onset times, called stimulus onset asynchrony (SOA). The spatial separation between the two sound sources does not affect the strength of the AAM sensation and only affects the perceived velocity of motion (Perrott and Strybel, 1977;Strybel et al, 1998). For example, Strybel et al (1990) reported that two sound bursts with durations of 50 ms and a SOA of 40-60 ms can produce an AAM with sound sources separated by as little as 6° or as much as 160°.…”
Section: Perception Of Moving Sound Sourcesmentioning
confidence: 99%
“…On the other hand, if the velocity is too great, a compression in overall extent may be perceived (Whitsel et aI., 1986), and minute changes in length of static patterns are readily detected (see, e.g., Schneider, Hughes, Epstein, & Bach-yRita, 1986). The influence of velocity on judgments of apparent motion can be substantial (Strybel, Span, & Witty, 1998) and will be discussed later. Furthermore, directional acuity, a gauge of the resolving power of the sensory system, is an additional factor that may vary with presentation parameters over body sites (Costanzo & Gardner, 1980;Essick, 1991;Gardner & Palmer, 1990;Gardner & Sklar, 1994) and is important in sequential pattern processing.…”
Section: Methodsmentioning
confidence: 99%